2018
DOI: 10.1089/zeb.2017.1469
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Accumulation of Ribosomal Multigene Families and Microsatellite DNAs in the XX/XY Sex Chromosome System in the Trans-Andean Catfish Pimelodella cf. chagresi (Siluriformes:Heptapteridae)

Abstract: This work constitutes the first cytogenetic characterization of a trans-Andean species of Heptapteridae. The catfish Pimelodella cf. chagresi from the Upper Rio Magdalena was studied, applying standard cytogenetic techniques (Giemsa, C-banding, and argyrophilic nucleolar organizer region [Ag-NOR]) and fluorescence in situ hybridization techniques using repetitive DNA probes: microsatellites (CA and GA) and ribosomal RNA (rRNA) multigene families (18S and 5S recombinant DNA [rDNA] probes). The species showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Although the association between sex chromosomes and (AG) 15 and (AC) 15 motifs have been reported in some bone fish [61,62], our data follow the general pattern found in other groups, showing pericentromeric and terminal clusters in autosomal chromosomes [50,62,66]. In this case, these microsatellite clusters might play a structural role and the pattern found here must be a result of different pressures that shaped the distribution of these SSRs in the karyotype in the P. wallacei.…”
Section: Plos Onesupporting
confidence: 85%
See 1 more Smart Citation
“…Although the association between sex chromosomes and (AG) 15 and (AC) 15 motifs have been reported in some bone fish [61,62], our data follow the general pattern found in other groups, showing pericentromeric and terminal clusters in autosomal chromosomes [50,62,66]. In this case, these microsatellite clusters might play a structural role and the pattern found here must be a result of different pressures that shaped the distribution of these SSRs in the karyotype in the P. wallacei.…”
Section: Plos Onesupporting
confidence: 85%
“…Although the association of SSRs motifs with sex chromosomes has been documented in many vertebrate groups [24,25,27,51,61,62], unfortunately, data about the distribution of SSRs in Potamotrygoninae species are limited to the present study. While most of SSRs used here showed amplification in several chromosomes, (GATA) 4 motif was associated with the X chromosome in P. wallacei (two sites in the female and one in males).…”
Section: Plos Onementioning
confidence: 90%
“…The use of AT-/GC-specific fluorochromes discovered great variability in the heterochromatin composition 56 . Simple repetitive sequences (e.g., microsatellites) are often accumulated in high copy numbers on the sex chromosomes in many taxa 57 - 59 , although the same repeats can be distributed throughout the genome in low copy numbers 55 . But in some species moderately repetitive sequences rather than highly repetitive DNA represent blocks of heterochromatin.…”
Section: Discussionmentioning
confidence: 99%
“…The location and number of the rDNA 5S are relatively variable occupying preferentially interstitial regions on one chromosome pair or two chromosome pairs (Table 1), in some cases syntenic with regions rDNA 18S, as already described by other authors. 11,16,25,[32][33][34] Gouveia et al 25,33 isolated 5S rDNA sequences and transposon (Tc1-mariner) from I. schubarti genome and found that transposable elements may be acting along these sequences, showing hybridization in some species of Heptapteridae and Pseudopimelodidae, and seem to be related to the movement of 5S rDNA genes in these fish genomes. Recently, Souza-Shibatta et al 35 reevaluated M. cottoides systematics, using morphological and molecular data, with sequence analysis of the COI (cytochrome oxidase I) gene.…”
Section: Heptapteridae Familymentioning
confidence: 99%